2012
DOI: 10.1016/j.ccr.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The ALKF1174L Mutation Potentiates the Oncogenic Activity of MYCN in Neuroblastoma

Abstract: SUMMARY The ALKF1174L mutation is associated with intrinsic and acquired resistance to crizotinib and cosegregates with MYCN in neuroblastoma. In this study, we generated a mouse model overexpressing ALKF1174L in the neural crest. Compared to ALKF1174L and MYCN alone, coexpression of these two oncogenes led to the development of neuroblastomas with earlier onset, higher penetrance and enhanced lethality. ALKF1174L/MYCN tumors exhibited increased MYCN dosage due to ALKF1174L-induced activation of the PI3K/AKT/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
276
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 282 publications
(299 citation statements)
references
References 43 publications
19
276
1
3
Order By: Relevance
“…The effect of VIP on invasion of these two cell lines was about 50-60%, even in the highly invasive and highly ALK is another therapeutic target considered for the treatment of NB [16]. Mutations of this receptor tyrosine kinase collaborate with MYCN in NB pathogenesis [8,10]. These mutations lead to constitutive activation of AKT signaling, a pathway known to inhibit MYCN proteasomal degradation [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of VIP on invasion of these two cell lines was about 50-60%, even in the highly invasive and highly ALK is another therapeutic target considered for the treatment of NB [16]. Mutations of this receptor tyrosine kinase collaborate with MYCN in NB pathogenesis [8,10]. These mutations lead to constitutive activation of AKT signaling, a pathway known to inhibit MYCN proteasomal degradation [45].…”
Section: Discussionmentioning
confidence: 99%
“…This tyrosine kinase receptor collaborates with MYCN for the development of most aggressive NB [8]. The F1174L ALK mutation is associated preferentially with MYCN amplification in NB and induces constitutive activation of the PI3K/AKT pathway [9,10]. This constitutive activation leads to oncogenic stabilization of MYCN protein [11].…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent phase I trial using the ALK inhibitor crizotinib in children with relapsed and refractory neuroblastoma has been completed [120], and further studies have identified synergistic combinations of ALK and mTOR inhibitors [121], suggesting a potential role for ALK inhibitors in the treatment of children with tumors with mutant ALK. Novel second-generation ALK inhibitors, such as ceritinib (LDK378), that are effective against the ALK F1174L mutant that is resistant to crizotinib [122,123] are currently being evaluated in clinical trials (NCT01742286).…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 99%
“…Most of these pathogenic variants are found within the tyrosine kinase domain of ALK and cause constitutive autophosphorylation and activation of the ALK protein and downstream cellular pathways, including the MAPK and RASrelated protein 1 signal pathways [9,27]. The PI3K (phosphatidylinositol 3-kinase)/Akt [10] and the JAK/STAT (Janus activated kinase/signal transducer and activator of transcription) pathways [28].…”
Section: Alk Variants In Neuroblastomamentioning
confidence: 99%
“…Activation of ALK increases the expression of MYCN by enhancing the activity of the MYCN promoter and stabilizing MYCN protein likely via activation of AKT and ERK pathways [9][10][11]. In vivo, compared to ALKF1174L and MYCN alone, co expression of these two oncogenes leads to the development of neuroblastoma tumors with earlier onset, higher penetrance and enhanced lethality [10,12,13]. In our recent study, neuroblastoma cells harboring both ALKF1174L mutation and MYCN amplification showed less responsive to an ALK inhibitor, crizotinib, comparing to other variants [14].…”
Section: Introductionmentioning
confidence: 99%